Glycolysis: an emerging regulator of osteoarthritis - Jiang, Dingming; Guo, Jianan; Liu, Yingquan; Li, Wenxin; Lu, Dezhao (Frontiers in Immunology, 2024)
Osteoarthritis (OA) has been a leading cause of disability in the elderly and there remains a lack of effective therapeutic approaches as the mechanisms of pathogenesis and progression have yet to be elucidated. As OA progresses, cellular metabolic profiles and energy production are altered, and emerging metabolic reprogramming highlights the importance of specific metabolic pathways in disease progression. As a crucial part of glucose metabolism, glycolysis bridges metabolic and inflammatory dysfunctions. Moreover, the glycolytic pathway is involved in different areas of metabolism and inflammation, and is associated with a variety of transcription factors. To date, it has not been fully elucidated whether the changes in the glycolytic pathway and its associated key enzymes are associated with the onset or progression of OA. This review summarizes the important role of glycolysis in mediating cellular metabolic reprogramming in OA and its role in inducing tissue inflammation and injury, with the aim of providing further insights into its pathological functions and proposing new targets for the treatment of OA.